Indicators of healthcare results: analysis of adverse events during hospital stays Indicadores de resultados para la asistencia: análisis de situaciones adversas durante la hospitalización Indicadores de resultados da assistência: análise dos eventos adversos durante a internação hospitalar - Camila Cristina Pires Nascimento; Maria Cecília Toffoletto; Leilane Andrade Gonçalves; Walkíria das Graças Freitas; Katia Grillo Padilha (Universidade de São Paulo, 2008)
This quantitative, retrospective study aimed to characterize adverse events (AE) in Intensive Care Units (ICU), Semi-Intensive Care Units (SCU) and Inpatient Units (IU), regarding nature, type, day of the week and nursing professionals / patient ratio at the moment of occurrence; as well as to identify nursing interventions after the event and AE rates. The study was performed at a private hospital in the city of São Paulo, Brazil. Two hundred twenty-nine AE were notified. The predominant events were related to nasogastric tubes (NGT) (57.6%), followed by patient fall (16.6%) and medication errors (14.8%). The nursing professionals /patient ratio at the moment of the event was 1:2 for the ICU, 1:3 for the SCU and 1:4 for the IU. A similar distribution was observed for the other days of the week. The nursing interventions were: repositioning the NGT (83.2%) and communication of the occurrence to the physician in case of medication errors (47.6%) and falls (55.2%). The highest AE rate was related to NGT. Estudio cuantitativo, retrospectivo que determinó las características de las situaciones adversas (SA) en la Unidad de Cuidados Intensivos (UCI), Unidad de Cuidados Semi-intensivos (UCS) y Servicio de Hospitalización (SH), en cuanto su naturaleza, tipo, día de la semana y la relación numérica trabajador / paciente. Asimismo, se identificó las intervenciones de enfermería y se calculo la tasa para SA. Realizado en un hospital privado de la ciudad de São Paulo. Se notificaron 229 SA, predominando los relacionados con la sonda nasogástrica (SNG) (57,6%), caídas (16,6%) y administración de medicamento (14,8%). La relación trabajador / paciente por día fue de 1:2 en UCI, 1:3 en UCS y 1:4 en SH. Las intervenciones de enfermería frente a estas situaciones fueron la recolocación de SNG (83,3%), la información al médico tanto en los casos de errores de medicación (47,6%), como en caídas (55,2%). La mayores tasas fueron observadas para los casos de SNG. Estudo quantitativo, retrospectivo, objetivou caracterizar eventos adversos (EA) nas Unidades de Terapia Intensiva (UTI), Semi-Intensiva (USI) e de internação (UI) quanto à natureza, tipo, dia da semana e relação funcionário/paciente no momento da ocorrência; identificar as intervenções dos enfermeiros após o evento e as taxas de EAs. Foi realizado em um hospital privado do município de São Paulo. Foi notificado o total de 229 EAs. Predominaram eventos relacionados à sonda nasogástrica (SNG) (57,6%), seguidos por queda (16,6%) e administração de medicamentos (14,8%). A relação funcionário/paciente, no momento do evento, era de 1:2 na UTI, 1:3 na USI e 1:4 na UI. Houve distribuição semelhante de ocorrências nos diferentes dias da semana. As intervenções de enfermagem foram recolocações da SNG (83,3 %) e comunicação da ocorrência ao médico nos casos de erros de medicação (47,6%) e queda (55,2%). A maior taxa de EAs foi relacionada à SNG.